Novel approaches to the fabrication of nanoscale devices - Balakrishnan, Nilanthy (2015)
This thesis describes the effects of a post-growth hydrogenation on as-grown samples and device structures based on III-N-V and III-V semiconductor compounds. The spectral response of quantum wells (QWs) or superlattices (SLs) are tuned by the control dissociation of N-H complexes using a focused laser beam (photon assisted dissociation) or by thermal annealing. These approaches could be implemented in other materials and heterostructure devices, and offer the advantage of enabling an accurate control of the spectral response of a device using a layer compound with a single N- concentration. A focused laser beam is also used to diffuse hydrogen from the p-type contact layer towards the III-N-V superlattice in the intrinsic region of a p-i-n diode, thus creating preferential injection paths for the carriers and creating nanoscale light emitting diodes. Opportunities for realizing a movable micron size-light emitting diode (-LED) are also demonstrated.